Perancangan Dan Implementasi Game Interaktif untuk Pembelajaran Digital pada Pelajaran TIK di MTsN 2 Banda Aceh Menggunakan Scracth - Zahwanul Ramadhana; Sarini Vita Dewi (Jurnal Teknologi Informasi dan Multimedia, 2026)
ICT learning currently demands the use of innovative learning media, to increase students' moti-vation and understanding of the material being studied, but at MTsN 2 Banda Aceh, convention-al methods such as lectures still dominate, which reduce students' motivation towards storage device and output device materials. This study aims to design, develop, and implement learning media in the form of scratch-based interactive games as a means of ICT (information and com-munication technology) learning to increase interactivity, learning motivation, and understand-ing of grade VIII students towards storage device and output device materials. Development re-search with a 4D model (Define, Design, Develop, Disseminate) and a mixed methods approach integrates quantitative data from questionnaires and qualitative data from observations and in-terviews. The results of media expert validation reached an average of 91% (strongly agree), while the assessment of 36 students showed an average score of 91% (very good) in the aspects of design, navigation, material understanding, and learning motivation. The Maze Tech game has been proven to be feasible, effective, and fun as an ICT digital learning media that supports inde-pendent and active learning. Furthermore, the Maze Tech game was developed with attention to the characteristics of junior high school students who tend to prefer visual and challenge-based learning. The integration of game elements, such as maze navigation, audio-visual feedback, and evaluative quizzes, provides a contextual and meaningful learning experience. This media also encourages active student involvement in the learning process, so it serves not only as a means of entertainment but also as an effective pedagogical tool. Therefore, the results of this study are ex-pected to contribute to the development of game-based digital learning media and serve as a ref-erence for educators in implementing ICT learning innovations in the madrasah environment.